Características morfofisiológicas de cafeeiros Coffea arabica L. - Batista, Luiz Antônio (2010)
Minas Gerais state is currently the greatest arabica coffee producer nationwide, responding for 52% production. South of Minas Gerais region responds for half state production.This work aimed to assess behavior of 15 cultivars selected by coffee plant genetic improvement in Minas Gerais (EPAMIG/UFLA/UFV/PROCAFE ), related to its tolerance and adaptation to dry environments. The experiment was installed at EPAMIG experimental farm in São Sebastião do Paraíso, South of Minas Gerais, in february 2005, delineation was in randomized blocs with three replications and one plant per parcel. Results have shown variations in evaluated characteristics such as foliar area, lenght and number of branches, stem diameter, plant height, hydric potential and foliar tissue thickness and stomastic characteristics. Skott-knott was applied to compare averages. Cultivars which highlighted in relation to other ones were Topázio MG 1190, Catucaí Amarelo 2 SL, Pau-Brasil MG 1, Obatã Vermelho IAC 1669-20 and Palma 2, therefore they were most indicated for the south region of Minas Gerais. Anatomic characteristics found in cultivars evaluated are indicative factors for selecting material tolerant to hydric deficit in areas able to cultivate coffee under hydric restriction.